Implementing the teams games tournament (TGT) cooperative learning model to enhance student learning outcomes on diversity is beautiful - Sarmila; Meriza Faradilla; Khairul Rizal (Pelita International Publishing, 2024)
This study aims to improve student learning outcomes on